The Prophetic Sunnah as a Legitimization of Polygamy: A Critical Review of Pengadilan Agama Decisions within the Framework of Islamic Law and Family Law - Pa'qih, Ibnu (Qanun: Jurnal Hukum Keluarga Islam, 2024)
This research examines decision number 4022/Pdt.G/2019/PAJT, in which the Panel of Judges granted a polygamy application on the grounds of carrying out the sunnah of the Prophet Muhammad, even though it did not fulfil the requirements set by the Marriage Law. The purpose of this study is to analyse the legal reasoning used by the Panel of Judges in granting the polygamy application and evaluate the decision from the perspective of Islamic law, family law in Indonesia, and legal philosophy. The method used in this research is a normative juridical approach with a qualitative nature, using a case approach and a statutory approach. The results showed that the decision did not fulfil the alternative and cumulative requirements stipulated by the Marriage Law, which should have resulted in the rejection of the application. In addition, the Panel of Judges in this decision failed to understand the conception of sunnah in Islamic law and tended to use a particularized interpretation of Surah al-Nisa verse 3. This research concludes that a more comprehensive and gender-equitable understanding of the sources of Islamic law is needed as well as consistency in the enforcement of existing rules in the Marriage Law related to polygamy. The impact of a gender-biased understanding and the inconsistency of judges in the application of the Marriage Law has the potential to exacerbate gender injustice and put women at risk of becoming victims of unfair and discriminatory practices. Therefore, reforms in the understanding and application of the law are urgently needed to create justice and well-being for all family members.